Comparative Study of Determinants of Nutritional Status of School Children in Different Indian Cities - DR. DIVYALEKSHMI P. S.; DR. APARNA BAGUL (The Bioscan, 2025)
Childhood undernutrition and overnutrition coexist in urban India, reflecting socioeconomic and regional disparities. This study compares the nutritional status of school-age children across seven major Indian cities—Ernakulam, Thiruvananthapuram, Mumbai, Delhi, Ahmedabad, Bengaluru, and Kolkata—using data from National Family Health Survey-5 (2019–21). Key indicators including stunting, wasting, underweight, and overweight are examined along with household, maternal, and environmental determinants. The findings highlight marked inter-city variation and underscore the role of maternal education, household wealth, sanitation, and urban living conditions in shaping child nutritional outcomes. KEYWORDS School children, Nutritional status, Urban India, NFHS-5, Stunting, Wasting.